MNCs in Rural Marketing - The Case of Pepsi and Coca Cola - Begde, Prasad (Indian Journal of Marketing, 2008)
The cola majors, Coke and Pepsi, are trying to penetrate deep into the rural markets with innovative pricing and marketing strategies.Apart from the high-decibel price wars and the usual battle over market shares, cola brands Coca-Cola and Pepsi have been in a quiet behind-the-scenes skirmish - to reach the rural masses. After an almost stagnant growth in this segment for the last two years, both Coke and Pepsi have made efforts this year to penetrate deep into the rural markets by substantially increasing their retailer and distribution network and with innovative pricing and marketing strategies.